Phosphodiesterases and cAMP Pathway in Pituitary Diseases - Bizzi, Mariana Ferreira; Bolger, Graeme B.; Korbonits, Márta; Ribeiro-Oliveira Jr., Antonio (Frontiers in Endocrinology, 2019)
Human phosphodiesterases (PDEs) comprise a complex superfamily of enzymes derived from 24 genes separated into 11 PDE gene families (PDEs 1-11), expressed in different tissues and cells, including heart and brain. The isoforms PDE 4, 7 and 8 are specific for the second messenger cAMP, which is responsible for mediating diverse physiological actions involving different hormones and neurotransmitters. The cAMP pathway plays an important role in the development and function of endocrine tissues while phosphodiesterases are responsible for ensuring the appropriate intensity of the actions of this pathway by hydrolyzing cAMP to its inactive form 5'-AMP. PDE1, PDE2, PDE4, and PDE11A are highly expressed in the pituitary, and overexpression of some PDE4 isoforms have been demonstrated in different pituitary adenoma subtypes. This observed over-expression in pituitary adenomas, although of unknown etiology, has been considered a compensatory response to tumorigenesis. PDE4A4/5 has a unique interaction with the co-chaperone aryl hydrocarbon receptor-interacting protein (AIP), a protein implicated in somatotroph tumorigenesis via germline loss-of-function mutations. Based on the association of low PDE4A4 expression with germline AIP-mutation-positive samples, the available data suggest that lack of AIP hinders the upregulation of PDE4A4 protein seen in sporadic somatotrophinomas. This unique disturbance of the cAMP-PDE pathway observed in the majority of AIP-mutation positive adenomas could contribute to their well-described poor response to somatostatin analogues and may therefore support a role in tumorigenesis.